A small population of an endemic mite species of the Gondwanan genus Austrotritia in Finland (Acari, Oribatida: Oribotritiidae). - Ritva H Penttinen; Lotta Hamalainen (the Entomological Society of Finland, the Lepidopterological Society of Finland, the Societas Entomologica Helsingforsiensis and the Entomological Club of the Zoological and Botanical Society of Turku., 2022)
The ptyctimous oribatid species, Austrotritia finlandica Niedbała & Penttinen, 2006, was described in Finland as the single representative of the genus in Europe. The main area of distribution of the Gondwanan genus Austrotritia covers the Oriental, Australian and southeastern Palaearctic Regions. In order to describe the more exact distribution and habitat of A. finlandica, more localities were studied in 2008-2012. Four hundred soil samples were studied from the southwestern archipelago and the islets along the Finnish coast of the Baltic Sea, and sixty tree hollows on an island. The number of records of the species increased from four to thirteen. Most of the islets where it was found were characterized by their small size (less than 1km2) and remote location. It is concluded that a small but permanent population of Austrotritia finlandica lives in a limited area in the SW archipelago of Finland.